Chirping ion cyclotron emission (ICE) on NSTX-U. (9th July 2021) - Fredrickson, E.D.; Gorelenkov, N.N.; Bell, R.E.; Diallo, A.; LeBlanc, B.P.; Lestz, J.; Podestà, M.; the NSTX team
Abstract: We report here on the discovery on NSTX-U of a qualitatively new type of non-thermal emission from plasmas in the ion-cyclotron frequency range (ICE). This new type of ICE is weakly damped, γdamp / ω ICE ≈ 0.14%, low order eigenmodes, excited by a fast ion population radially located near an internal transport barrier. The ICE appears as repetitive bursts with durations of ≈1 ms, and the bursts exhibit frequency chirps upwards and/or downwards with maximum δf / f ≈ 1%. We refer to this chirping ICE as ch-ICE. The bursts are longer than the typical ICE bursts of ≈100 μ s reported previously for NSTX and NSTX-U, for simplicity, NSTX(-U). The chirping resembles that seen in modeling of weakly unstable fast particle driven instabilities (cf, Berk et al 1997 Phys. Lett. A 234 213). These data also provide some preliminary indications of non-linear coupling between the ch-ICE harmonics. Despite extensive experimental and theoretical studies of ICE, theoretical understanding of ICE remains qualitative at best. The detailed experimental observations of ICE from NSTX(-U) find a wide variation in the ICE characteristics. The new observations of ch-ICE presented here, combined with the characteristics of ICE on NSTX(-U) previously reported (Fredrickson et al 2019 Phys. Plasmas 26 032111), could guide the development of more complete theoretical models of ICE.